Unsymmetrical phthalocyanines with alkynyl substituents - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The synthesis of unsymmetrically substituted metallophthalocyanines (M = Zn, Ni, Co) bearing two phenylethyl moieties and six alkythio substituents was achieved by co-cyclotetramerization of two different phthalonitrile derivatives, namely 4,5-di(hexyl-thio)phthalonitrile and 4,5-di(phenylethynyl)phthalonitrile in the presence of zinc, cobalt or nickel salts. In contrast to the totally alkyne substituted phthalocyanines, these partially alkyne-containing derivatives are more soluble and their Q band absorptions are red-shifted when compared with all alkylthio phthalocyanines. Electrochemical properties of the phthalocyanines were studied by cyclic voltammetry. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; unsymmetrical; phenylacetylene; cyclic voltammetry; PUSH-PULL PHTHALOCYANINES; ZINC PHTHALOCYANINE; ELECTROCHEMICAL PROPERTIES; BRANCHED BULKY; METAL-FREE; PORPHYRAZINES; METALLOPHTHALOCYANINES; FILMS